If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8s(8 + 6s) = 20 (8 * 8s + 6s * 8s) = 20 (64s + 48s2) = 20 Solving 64s + 48s2 = 20 Solving for variable 's'. Reorder the terms: -20 + 64s + 48s2 = 20 + -20 Combine like terms: 20 + -20 = 0 -20 + 64s + 48s2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-5 + 16s + 12s2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-5 + 16s + 12s2)' equal to zero and attempt to solve: Simplifying -5 + 16s + 12s2 = 0 Solving -5 + 16s + 12s2 = 0 Begin completing the square. Divide all terms by 12 the coefficient of the squared term: Divide each side by '12'. -0.4166666667 + 1.333333333s + s2 = 0 Move the constant term to the right: Add '0.4166666667' to each side of the equation. -0.4166666667 + 1.333333333s + 0.4166666667 + s2 = 0 + 0.4166666667 Reorder the terms: -0.4166666667 + 0.4166666667 + 1.333333333s + s2 = 0 + 0.4166666667 Combine like terms: -0.4166666667 + 0.4166666667 = 0.0000000000 0.0000000000 + 1.333333333s + s2 = 0 + 0.4166666667 1.333333333s + s2 = 0 + 0.4166666667 Combine like terms: 0 + 0.4166666667 = 0.4166666667 1.333333333s + s2 = 0.4166666667 The s term is 1.333333333s. Take half its coefficient (0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. 1.333333333s + 0.4444444442 + s2 = 0.4166666667 + 0.4444444442 Reorder the terms: 0.4444444442 + 1.333333333s + s2 = 0.4166666667 + 0.4444444442 Combine like terms: 0.4166666667 + 0.4444444442 = 0.8611111109 0.4444444442 + 1.333333333s + s2 = 0.8611111109 Factor a perfect square on the left side: (s + 0.6666666665)(s + 0.6666666665) = 0.8611111109 Calculate the square root of the right side: 0.927960727 Break this problem into two subproblems by setting (s + 0.6666666665) equal to 0.927960727 and -0.927960727.Subproblem 1
s + 0.6666666665 = 0.927960727 Simplifying s + 0.6666666665 = 0.927960727 Reorder the terms: 0.6666666665 + s = 0.927960727 Solving 0.6666666665 + s = 0.927960727 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + s = 0.927960727 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + s = 0.927960727 + -0.6666666665 s = 0.927960727 + -0.6666666665 Combine like terms: 0.927960727 + -0.6666666665 = 0.2612940605 s = 0.2612940605 Simplifying s = 0.2612940605Subproblem 2
s + 0.6666666665 = -0.927960727 Simplifying s + 0.6666666665 = -0.927960727 Reorder the terms: 0.6666666665 + s = -0.927960727 Solving 0.6666666665 + s = -0.927960727 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + s = -0.927960727 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + s = -0.927960727 + -0.6666666665 s = -0.927960727 + -0.6666666665 Combine like terms: -0.927960727 + -0.6666666665 = -1.5946273935 s = -1.5946273935 Simplifying s = -1.5946273935Solution
The solution to the problem is based on the solutions from the subproblems. s = {0.2612940605, -1.5946273935}Solution
s = {0.2612940605, -1.5946273935}
| 8x^8y^6+40x^6y^5+24xy= | | X^2+8x-9=I | | 7/12f=3/5 | | (x-y)dx+xdy=0 | | 7+3(3n+4)-n= | | 8-3x=x-2y | | 18=24(x/6.9) | | 12/15=p/100 | | 45+8x=237 | | 2=ln(x+9) | | 18=0.5x | | -8/9c-(-24) | | a+3=2a+2 | | 7.50+.35x=13.45 | | 871.87/3181.82 | | 3(2x+9)-(6-x)=24 | | 1.5=-3w | | y^2-16y-80= | | 2x+x=246 | | 3.6=12n | | 6a-7=5a+2 | | 8x^3+4x^2-2x+1= | | 3x^2+4x=12 | | f(x)=(0.2)4*(-1) | | 2a-5=a+3 | | .40x=2.30 | | X=176 | | -2x+7=33 | | x*(1.10)=3500 | | 4x-(-6)=38 | | -6(5p+4)-34=2(2p+5) | | 0.50(x-4)/-3 |